2021
DOI: 10.1190/geo2019-0570.1
|View full text |Cite
|
Sign up to set email alerts
|

Deep-seismic-prior-based reconstruction of seismic data using convolutional neural networks

Abstract: The reconstruction of seismic data with missing traces has been a long-standing issue in seismic data processing; deep learning methods have attracted significant attention in seismic data reconstruction. One barrier associated with these deep-learning based reconstruction methods is the need for large training datasets, which are difficult to acquire owing to physical or financial constraints in practice. A novel method for the recovery of incomplete seismic data without the need of training datasets was deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…This problem is very similar to compressed sensing as seismic data reconstruction is performed using sub-sampled data. In [134], a UNNP-based algorithm named DSPRecon was proposed for the reconstruction of seismic data. A U-Net with skip connections was used in the proposed UNNP framework that learns the deep prior for seismic image reconstruction.…”
Section: Seismic Data Reconstructionmentioning
confidence: 99%
“…This problem is very similar to compressed sensing as seismic data reconstruction is performed using sub-sampled data. In [134], a UNNP-based algorithm named DSPRecon was proposed for the reconstruction of seismic data. A U-Net with skip connections was used in the proposed UNNP framework that learns the deep prior for seismic image reconstruction.…”
Section: Seismic Data Reconstructionmentioning
confidence: 99%
“…Chai et al (2020) applied a convolution neural network based on an encoder-decoder style U-Net (Ronneberger et al, 2015) to regularize regular/irregular seismic data, which showed better performance than the fast-generalized Fourier transform method (Naghizadeh & Sacchi, 2009) on irregular seismic data. Liu et al (2021) proposed a U-Netbased deep-seismic-prior method. This method does not require a large data set and can complete regularization with only one undersampled seismic data set.…”
Section: 1029/2022jb024122mentioning
confidence: 99%
“…In recent years, deep learning has achieved outstanding successes in a variety of domains, including computer vision (Ferdian et al, 2020;Manor and Geva, 2015) and medical image processing (Li et al, 2021;Tavoosi et al, 2021), with its powerful representing ability. In the field of geophysics, deep learning methods have also been applied to many research directions recently, such as seismic inversion (Shahbazi et al, 2020;Wu et al, 2020;, fault analysis (Wu et al, 2019;Lin et al, 2022;Wang et al, 2022;Zhu et al, 2022), denoising (Qiu et al, 2022;Jiang et al, 2022;Yang et al, 2021;Yang et al, 2022), and interpolation (Liu et al, 2021;Yu and Wu, 2022).…”
Section: Introductionmentioning
confidence: 99%